Ten-year experience retrospective in investigation of the frequency of sex chromosome aneuploidies diagnosed in a reference medical center in Türkiye - Tutgun Onrat, Serap; Keleş, Yağmur; Aydın, Saliha; Etiler, Rana; Aktaş, Zeynep (International Journal Of Community Medicine And Public Health, 2022)
Background: Sex chromosome aneuploidies (SCAs) are characterized by the gain or loss of entire or parts of sex chromosomes. Methods: In 5212 cases studied over the last 10 years in Medical Genetics Department, we found 3793 (72.78%) other chromosomal establishments and 1419 (27.22%) sex chromosomal aneuploidies using the retrospective archive-file scanning method. Results: 839 (31.32%) of the 1419 cases with anomalies were female, and 580 (22.8%) were male. While Triple X-Super Female Syndrome 423 (15.8%) is the most common in women, Klinefelter Syndrome 508 (20.0%) is the most common in men. Among the cases sent to our outpatient clinic for various indications (prediagnosis) for karyotype analysis, 1447 (54.0%) in women and 1193 (47.1%) in men were the cases with a prediagnosis of habitual abortion; followed by 298 (11.1%) infertility in women and 350 (13.8%) in men. While 167 (6.6%) people were sent with the preliminary diagnosis of azoospermia in men, it was determined to be 124 (4.6%) in women with primary amenorrhea. In the analysis we made according to the diagnosis, 1839 (68.7%) women and 1954 (77.1%) men were found to be normal. While the most important diagnosis is Triple X-Super Female syndrome 423 (15.8%) in women, Klinefelter syndrome 508 (20.0%) is the first in men. Turner Syndrome is found in 315 (11.8%) women, while Jacob’s syndrome (47, XYY) is detected in 13 (0.5%) men. Conclusions: As a result, the retrospective evaluation of 10-year cytogenetic analyses of these case groups contributes to the creation of regional data.